Synergistic effects aided the growth of black locust in reclaimed areas of semi-arid open-pit coal mines - Shi, Zeyu; Bai, Zhongke; Guo, Donggang; Ma, Xu; Chen, Meijing; Li, Shuai (Frontiers in Ecology and Evolution, 2023)
The mining of mineral resources has caused serious damage to the ecosystems of mining areas, resulting in the degradation of large areas of vegetation. In the Loess Plateau in particular, the ecological environment is fragile, and soil erosion is serious. It is urgent to restore vegetation and to improve the quality of the damaged environment. In the process of restoring the vegetation in the Pingshuo opencast mining area, this paper investigates the growth rates of species and the factors that affect these rates. The results showed that the maximum growth rate of R. pseudoacacia was 0.25 m/year in Mingled stand and 0.23 m/year in pure stand. The growth rate of R. pseudoacacia in Mingled stand was higher than that in pure stand, and the diversity indicators in the Mingled stand plots were higher than those in the pure stand plots. The stepwise regression analysis of the species diversity index, soil, and climate with the growth rate of the two plots showed that Margalef’s richness index had a significant effect on the growth rate of R. pseudoacacia in Mingled stands. This indicates that the R. pseudoacacia in our study area grows faster in Mingled stand and that the U. pumila and A. altissima that belong to the broad-leaved forest will grow together with R. pseudoacacia. The configuration pattern of broad-leaved pure stand is more singular than that of broad-leaved mingled stand, so the pure stand is not more suitable for vegetation restoration in the mining area.